2009
DOI: 10.1136/bmj.b1458
|View full text |Cite
|
Sign up to set email alerts
|

Participation in life situations of 8-12 year old children with cerebral palsy: cross sectional European study

Abstract: Objectives To evaluate how involvement in life situations (participation) in children with cerebral palsy varies with type and severity of impairment and to investigate geographical variation in participation.Design Cross sectional study. Trained interviewers visited parents of children with cerebral palsy; multilevel multivariable regression related participation to impairments, pain, and sociodemographic characteristics.Setting Eight European regions with population registers of children with cerebral palsy;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
205
2
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(230 citation statements)
references
References 45 publications
11
205
2
12
Order By: Relevance
“…Studies have shown that children with CP and pain are less likely to participate in life situations and have a lower quality of life. 1,2 Although clinicians are responsible for identifying and treating pain, communication challenges of the child with CP and multiple pain etiologies often complicate this process. 3 Pain in children and youth with CP is reported in the literature by 14% to 73% of caregivers and in 60% of subjects who can self-report.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that children with CP and pain are less likely to participate in life situations and have a lower quality of life. 1,2 Although clinicians are responsible for identifying and treating pain, communication challenges of the child with CP and multiple pain etiologies often complicate this process. 3 Pain in children and youth with CP is reported in the literature by 14% to 73% of caregivers and in 60% of subjects who can self-report.…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels of mobility participation were associated with higher levels of pain and reduced walking ability in a population-based sample of young people with CP. 5 In this paper, selfreported total fatigue was higher in females than in males, and was associated with living in areas of low socioeconomic status and with low physical activity, while it was not associated with body weight or functional impairment level. The lack of any relationship between the degree of functional impairment (Gillette Functional Assessment Questionnaire) and self-reported fatigue may be related to the fact that the sample of children included in the study had spent a good deal of their childhood in therapy/adaptive programs designed to enhance their physical function.…”
mentioning
confidence: 58%
“…Fragala-Pinkham et al 5 have helped move this research question forward in their paper describing the validation of the OMNI Walk/Run Rating of Perceived Exertion (OMNI-RPE) scale for ambulatory children and adolescents with CP. In this study the authors recognize the importance of measuring perceived exertion for individuals with CP in a practical manner.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9,11,12 Unrecognized pain can have negative implications on health and quality of life, with the possibility that childhood pain will persist and progress into adulthood. 1,9,11,[13][14][15][16][17][18][19][20] Chronic pain can significantly interfere with participation in daily living activities, both as a result of limited mobility resulting from the source of pain and fear-driven avoidance of specific activities. 8,15,16,[21][22][23][24] Childhood chronic pain has been associated with disturbances in sleep, increased fatigue, depression, and decreased physical functioning.…”
mentioning
confidence: 99%